The role of sacred natural sites (SNS) and related traditional ecological governance systems and their legal recognition to enhance community wellbeing and resilience - Zeleke, Mersha Yilma (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2020.